Stamping out wildlife disease: Are hunter‐funded stamp programs a viable option for chronic wasting disease management? - Danielle J. Ufer; Sonja A. Christensen; David L. Ortega; Nick Pinizzotto; Krysten Schuler (Conservation Science and Practice, 2022)
Abstract Stamp programs are a financial mechanism that can provide funding from stakeholders for conservation efforts. Sufficient funding is foundational for the management of wildlife and natural resources, especially for infectious disease control for diseases like chronic wasting disease (CWD) in deer. This study uses contingent valuation in a nationwide hunter survey to evaluate the potential for state‐managed stamp programs to fund CWD prevention or management efforts. Results indicate that on average hunters are willing to pay between $11.45 and $21.93 for a voluntary CWD stamp. Willingness to pay varied by geographical location, CWD concern level, education, and participation in an archery season. Based on our analysis, stamp programs to fund CWD prevention or management may be a viable avenue for state conservation agencies to pursue.